HUBUNGAN KOLESTEROL NON-HDL TERHADAP FUNGSI KOGNITIF PADA PASIEN STROKE ISKEMIK DENGAN DEFISIT NEUROLOGIS RINGAN - Aylenia Lysandra; Budi Riyanto Wreksoatmodjo; Josephine Retno Widayanti (PERDOSNI, 2020)
Introduction: Ischemic stroke patients have higher risk of cognitive decline. Severity of cognitive impairment depends on the severity of neurological deficit. The severity of cognitive impairment is also affected by abnormal non-HDL cholesterol level which includes atherogenic lipid that causes atherosclerosis. Aim: Understanding the association of non-HDL cholesterol and cognitive function in mild stroke patients at Atma Jaya Hospital in 2014-2018. Methods: A cross-sectional study by analyzing stroke registry patients (115 subjects). Data is analyzed by using Chi-square test and Fisher exact test. Results: Total sample of this research is 115 respondents. Mean age was 58±11,286 years old and 30,4% graduated from senior high school. 38,3% have cognitive impairment measured by Mini Mental State Examination (MMSE), of which 79.5% have abnormal non-HDL cholesterol. Meanwhile, 70,4% have cognitive impairment measured by Montreal Cognitive Assessment Indonesian Version (MoCA-Ina), of which 76.5% have abnormal non-HDL cholesterol. Cognitive function measured by MMSE and MoCA-Ina has no significant association with non-HDL cholesterol (respectively). Discussion: This research contradicted the previous research. It is suspected that there is no direct relationship between non-HDL cholesterol and cognitive function. Besides, cholesterol acts as antioxidant, has a role in neurotransmission and has a protective effect. Discussion: Cognitive function in patients with mild stroke, measured by MMSE and MoCA-Ina, is not associated with non-HDL Cholesterol. Keywords: Cognitive function, ischemic stroke, mild stroke, non-HDL cholesterol